A preliminary phonetic-acoustic study on the voiceless nasal consonants of the Resígaro (Arawak) language - Jiménez Peña, Jhon (2021)
This paper provides a first acoustic description of the nasal voiceless consonants of the Resígaro (Arawak) language. Some features such as acoustic structure, frequency and intensity of the most prominent peak and duration of this consonant class are explored. The particularities found were compared with those of other languages that present these sounds in order to find similarities and differences, as well as to catalog them preliminarily in some typological group. In addition, the methodology used for data collection, data analysis and conclusions are presented.